Controlling System of Material Inventory - Mega Mayasari; Boby Irman (Journal of Applied Accounting and Taxation, 2016)
This Research purposes to determine the application system controlling about inventory especially in the store or warehouse. The analytical method used is descriptive method with data from the company are weekly report of weld and factory consumable and with the interview process. The analysis technique used was to evaluate the activity of inventory control, implementation of inventory control and procedures should preferably be performed company. The results showed that in the store does not undergo inventory control activities such as conducting document authorization system, the division of task and the others. Based on the result of study it can be concluded that the existing inventory control especially in the store or warehouse did not go well and properly.